2014
DOI: 10.5137/1019-5149.jtn.11235-14.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the surgical results for foramen magnum decompression with and without duraplasty in chiari malformation type 1

Abstract: AIM:The surgical results for foramen magnum decompression (FMD) with and without duraplasty in Chiari Malformation type 1 (CM-1) were compared retrospectively. MATErIAL and METHods:Thirty-nine cases of CM-1 with and without syringomyelia (SM) were included. There were 18 patients in the nonduraplasty and 21 in the duraplasty group. Syringomyelia, tonsillar herniation (TH), preoperative symptom duration, and postoperative SM size were compared. rEsuLTs: No significant difference was found between improvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…There were studies in which the population consisted of both pediatric and adult patients. However, to maintain a high degree of applicability for pediatric patients, a number of studies 3,10,24,29,42,52,65 in which clinical outcomes could not be discerned between the children and adult groups were not included. Excluding these studies could have diminished the significance of further outcomes, such as syrinx and scoliosis improvement, and introduced a greater degree of heterogeneity between studies observed in the outcomes of this study, despite the lack of publication bias.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…There were studies in which the population consisted of both pediatric and adult patients. However, to maintain a high degree of applicability for pediatric patients, a number of studies 3,10,24,29,42,52,65 in which clinical outcomes could not be discerned between the children and adult groups were not included. Excluding these studies could have diminished the significance of further outcomes, such as syrinx and scoliosis improvement, and introduced a greater degree of heterogeneity between studies observed in the outcomes of this study, despite the lack of publication bias.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…On the other hand Benjamin et al recommended PFD without opening the dura for the vast majority of symptomatic patients with CM-I. He recommended opening the dura in patients with rapidly progressive neurological deficits, rapidly progressive scoliosis with syrinx [15].…”
Section: Discussionmentioning
confidence: 99%
“…Overview of the literature about craniectomy size, C1 arch removal, duraplasty, and tonsillar resection and arachnoid dissection are listed in ►Tables 6 to 9, respectively. 10,[12][13][14][15][16][17][18][19][20]…”
Section: Surgical Techniques Followed Its Correlation To Underlying mentioning
confidence: 99%